Analisis Manajemen Kepemimpinan dalam Mendukung Semangat Belajar Santriwati di Kelas pada Pondok Pesantren Nurul Faizah Surabaya - Akhmad Fauzi; Priti Artika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze leadership management in supporting female students' enthusiasm for learning in class at the Nurul Faizah Islamic Boarding School as well as knowing the female students' views on this matter. This research is qualitative. Data collection was carried out using interviews, observation, and documentation. Interviews were conducted only with a few informants who fully understood the mechanisms applied to the Islamic boarding school, such as caregivers, the head of the boarding school, the head of each class, and one of the female students at the boarding school. This research shows that the Nurul Faizah Islamic boarding school has carried out learning activities adequately and systematically, and the existence of competent Ustadz/Ustadzah in their field is expected to positively influence female students to be enthusiastic about learning. However, the drawback is controlling the presence of students who still need to improve. In conclusion, the policy taken by a boarding school leader is expected to increase the enthusiasm or enthusiasm for learning for female students, especially learning in class at Islamic boarding schools. Keywords: Eager to Learn, Leadership, Management